Ordinary Language and Dialogue in Entrepreneurship - Mitchell, J. Robert; Israelsen, Trevor L.; Mitchell, Ronald K.; Hua, Wei (Academy of Management Review, 2024)
We build on the work of Ramoglou and McMullen (2022) by suggesting that for the philosophy of ordinary language in entrepreneurship to meet its potential in research and practice, a deeper and more explicit treatment of the interactive aspects of language is needed. We focus on how additional attention to the interactive nature of ordinary language in the contexts of entrepreneurial action can help to inform what Ramoglou and McMullen describe as entrepreneurial work. The approach to such interaction that we suggest here centers on the dialogue that emerges in the interactions between entrepreneurs and potential stakeholders. Such an approach, we argue, can enable a conceptualization of entrepreneurial work that exists as something bigger than the interests of the entrepreneur alone. We accordingly suggest that theorizing such interaction can reveal the broader potential of the ordinary language philosophy in the analysis of what entrepreneurs do as they pursue opportunities.